Peningkatan Partisipasi Masyarakat (D/S) melalui Pedekatan Home Care dengan Konseling di Puskesmas Lingkar Barat Kota Bengkulu - Desri Suryani; Kusdalinah; Meriwati; Adelia Ajelika; Afifah Putri Azzahra; Anggryani Margaretha; Aprita Dwi Putri Elliza; Cicilia Fransiska; Elsha Cristin Sipahutar; Lista; Nevike Amanda P; Riski Amalia; Shafiyyah Ummu K; Tadzkia Maghfira (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
The level of community participation in utilizing the Integrated Service Post is quite good, but there are still some integrated health posts whose achievements have not reached the national target. Many factors cause a lack of community participation, including work, knowledge, age and education of mothers and family support. The purpose of the activity is to increase the scope of community participation through home care socialization activities with counseling for parents of toddlers. The method of activity is carried out by providing education and counseling as well as monitoring the nutritional status of toddlers by weighing the weight, height, and length of toddlers, accompanied by parents. The activity was carried out for 10 days in the Lingkar Barat Health Center area of ​​Bengkulu City. The results of the home care socialization activity can increase the participation of mothers to come to the Integrated Service Post, in addition, it can increase mothers' knowledge about the nutritional status of toddlers, and the benefits of coming to the Integrated Service Post. Conclusion: there is an increase in community participation after home care activities are carried out with the provision of education and counseling.